Ambient intelligence and simulation in health care virtual scenarios - Abelha, António (2007)
The success of change depends greatly on the ability to respond to human needs and to bridge the gap between humans and machines, and understanding the environment. With such experience, in addition to extensive practice in managing change, knowledge sharing and innovation, it would be interesting in offering a contribution by facilitating a dialogue, knowledge café (i.e. bringing in knowledge) on these issues, and how to apply them to new and altering scenarios. On the other hand, when one comes into the area of health care, one major limitation felt by those institutions, is in the selection process of physicians to undertake a specific task, where there is a lack of objective, of validated measures of human performance. Indeed, objective measures are necessary if simulators are to be used to evaluate the skills and training of medical practitioners and teams or to evaluate the impact of new processes or equipment design on the overall system performance. Therefore, in this paper it will be presented a logical theory of Situation Awareness (SA) and discusses the methods required for developing an objective measure of SA within the context of a simulated medical environment, as the one referred to above. Analysis and interpretation of SA data for both individual and team performance in health care are presented.